2018
DOI: 10.1149/2.0361815jes
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Chlorine Selectivity through Weakening of Oxygen Adsorbates at Surface in Cu Doped RuO2 during Seawater Electrolysis

Abstract: During seawater electrolysis, both oxygen and chlorine evolve at anode and their selectivity can be modulated through variation of surface and electronic structure of the electrocatalyst. In this context, the selectivity toward chlorine evolution reaction (CER) during seawater electrolysis using electrodeposited Cu-doped RuO 2 with lower doping concentration (2%) has been found to better than RuO 2 . Though Cu does not behave as an active site it reduces the binding energy of oxygen evolution reaction (OER) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Ru based catalysts have shown selectivity for both OER and ClER. While most of the Ru based studies had a focus on the ClER35,[50][51][52][53] or the fundamental understanding of the ClER on ruthenium titanium oxide (RTO)46,[54][55][56] , there are a few studies that reported enhanced selectivity towards OER on someRu-based catalysts. Some speculated that doping of Zn into RuO2 crystal structure caused a rearrangement of the local atomic structure in the vicinity of the Zn ions, enhancing the oxygen evolution process at positive potentials and, overall, improving the selectivity of the OER in chloride containing acidic media 57 .…”
mentioning
confidence: 99%
“…Ru based catalysts have shown selectivity for both OER and ClER. While most of the Ru based studies had a focus on the ClER35,[50][51][52][53] or the fundamental understanding of the ClER on ruthenium titanium oxide (RTO)46,[54][55][56] , there are a few studies that reported enhanced selectivity towards OER on someRu-based catalysts. Some speculated that doping of Zn into RuO2 crystal structure caused a rearrangement of the local atomic structure in the vicinity of the Zn ions, enhancing the oxygen evolution process at positive potentials and, overall, improving the selectivity of the OER in chloride containing acidic media 57 .…”
mentioning
confidence: 99%
“…(b) Increase in packing densities of active sites on the exposed surface facet of electrocatalyst. (c) Inducing surface‐strain through via dopants (Akhade & Kitchin, 2012; Busch et al, 2016; Kishor et al, 2015; Kishor, Saha, Parashtekar, & Pala, 2018; McFarland & Metiu, 2013; Pala et al, 2009; S. Saha, Kishor, & Pala, 2018a; S. Saha, Kishor, & Pala, 2018b), and ligands result in the exposure of non‐native facets with unconventional morphologies (Rastogi et al, 2019) or by forming thin films (Pala & Metiu, 2007; Y. Yu et al, 2014). In addition to these, use of NNPs could be an additional strategy to increase the electrocatalytic activity without tinkering with the stoichiometry/chemical composition of the material since the electronic structure is highly dependent on the coordination symmetry (P. Chen et al, 2016; Z. Xu & Kitchin, 2015).…”
Section: Electrocatalytic and Photo‐electrocatalytic Reaction And Nonmentioning
confidence: 99%
“…(b) Increase in packing densities of active sites on the exposed surface facet of electrocatalyst. (c) Inducing surface-strain through via dopants (Akhade & Kitchin, 2012;Busch et al, 2016;Kishor et al, 2015;Kishor, Saha, Parashtekar, & Pala, 2018;McFarland & Metiu, 2013;Pala et al, 2009;S. Saha, Kishor, & Pala, 2018a;S.…”
Section: Electrocatalytic and Photo-electrocatalytic Reaction And Non-native Polymorphmentioning
confidence: 99%
“…Recent studies report that the inclusion of CuO x enhances the sensitivity and selectivity properties of RuO x -based sensors used to monitor the dissolved oxygen and also improves the resistance to fouling [25]. As dopant in RuO x -electrocatalyst, CuO x has been found to improve the intrinsic oxygen evolution reaction (OER) activity in acidic conditions [26] but also to promote the selectivity toward chlorine evolution reaction (CER) during electrolysis of marine water [27].…”
Section: Introductionmentioning
confidence: 99%